2014
DOI: 10.1371/journal.pone.0099114
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Respiratory Papillomatosis: HPV Genotypes and Risk of High-Grade Laryngeal Neoplasia

Abstract: Patients with recurrent respiratory papillomatosis (RRP) in Norway treated between 1987 and 2009 were recruited to this cohort study. They were followed from disease onset and data recorded until January 2012. Here, we describe the distribution of human papillomavirus (HPV) genotypes, the prevalence of multiple HPV infections, and the risk of high-grade laryngeal neoplasia and respiratory tract invasive carcinoma in a large cohort of patients with RRP. We also examined whether HPV genotype, gender, age or clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
81
1
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 58 publications
9
81
1
8
Order By: Relevance
“…While persistent Human Papillomatosis Virus (HPV) type 6 or 11 virus infection is often associated with JORRP development5, emerging evidences showed that immune responses against HPV type 6 or 11 virus infection are the determinants of JORRP outcome6. It has been suggested that impaired cellular immune response in patients with JORRP support sustained HPV-6/11 infection and prevent HPV virus from clearance.…”
mentioning
confidence: 99%
“…While persistent Human Papillomatosis Virus (HPV) type 6 or 11 virus infection is often associated with JORRP development5, emerging evidences showed that immune responses against HPV type 6 or 11 virus infection are the determinants of JORRP outcome6. It has been suggested that impaired cellular immune response in patients with JORRP support sustained HPV-6/11 infection and prevent HPV virus from clearance.…”
mentioning
confidence: 99%
“…En diferentes estudios reportan este dato como muy influyente en la infección por el VPH, sobre todo la práctica del sexo oral y la tenencia de múltiples parejas sexuales; (Omland et al, 2014), con respecto al antecedente de papilomatosis respiratoria recurrente, solamente en una (1) de las pacientes (femenina) existía el antecedente dudoso de esta afección, incluso con traqueotomía previa 20 años antes a la revisión del caso. Como fue mencionado antes, existe evidencia científica en la cual se considera a la papilomatosis laríngea recurrente como factor de riesgo para la carcinogénesis.…”
Section: Discussionunclassified
“…According to international studies, the following percentages of disease cases are attributable to HPV: 100% for cervical cancer, 88.0% for anal cancer, 39.7% for vulvar cancer, 78.0% for vaginal cancer, 50.0% for penile cancer, 30.8% for oropharyngeal cancer, 2.2% for oral cavity cancer, 2.4% for laryngeal cancer,4 18 19 90% for genital warts1 and 90% for benign neoplasms of the larynx (ie, RRP) 2. As data on HPV-attributable percentages of CIS cases were unavailable, we assumed that these percentages were equal to those previously reported for cancer cases of corresponding anatomical sites.…”
Section: Methodsmentioning
confidence: 99%
“…Twelve high-risk types of HPV are associated with cancers of the cervix, vagina, vulva, anal canal, penis, oropharynx, oral cavity, larynx and oesophagus (online supplementary reference w1) while the low-risk HPV types (mainly types 6 and 11) chiefly cause genital warts in men and women1 and recurrent respiratory papillomatosis (RRP) 2…”
Section: Introductionmentioning
confidence: 99%